Veteran‐Directed Care Recipients Living in Rural Areas Have Fewer Incidents of Potentially Avoidable Health care Use Compared to Recipients of Other Purchased Care Services - Yuan, Y. (Health Serv Res, 2020)
RESEARCH OBJECTIVE: The Veteran‐Directed Care (VDC) program supports Veterans at risk of nursing home placement—those with multiple chronic conditions and functional limitations—as well as their caregivers. VDC enrollees receive a monthly budget that can be used to hire family, friends, and neighbors as paid caregivers. Patients living in rural areas have limited access to agency care and may be uniquely likely to benefit from the choice and flexibility afforded by VDC. The objective of this study is to compare Veterans’ health care use in the 12 months before and after VDC service initiation to utilization among recipients of other VA‐purchased care programs (homemaker/home health aide, home respite, and contract adult day health care), and identify any differential benefits by rural/urban location. STUDY DESIGN: Using VA administrative data on health status and health care use, we compared the difference in outcomes from pre‐ to postinitial enrollment in the VDC program with the difference in outcomes from pre‐ to postinitial enrollment in other purchased care programs in FY17 for patients living in rural or urban areas. Our primary outcomes were monthly incidences of acute care admissions, nursing home admissions, hospice admissions, and ED visits at VA Medical Centers (VAMCs). We used fixed‐effects logistic models on a matched cohort of VDC and non‐VDC enrollees. We examined the robustness of our results using different model specifications and different definitions of postperiod and sample selection criteria. Analyses were stratified by urban/rural location. POPULATION STUDIED: Our cohort included 37,407 Veterans receiving at least one VHA‐purchased care service in FY17 in one of 38 VAMCs. Patients in the VDC group (n = 965) were from 21 active sites where VDC was regularly offered. Patients in the comparison groups were from the 21 active sites (n = 21,117) and 17 inactive sites (n = 15,325) that indicated interest in implementing VDC. PRINCIPAL FINDINGS: Rural, but not urban, VDC enrollees had significantly fewer acute care and emergency department visits over time, relative to recipients of other purchased care services (acute care, rural: odds ratio [OR] = 0.72, 95% CI = [0.56, 0.92], urban: OR = 0.95, [0.79, 1.13]; ED visits, rural: OR = 0.69, [0.54, 0.89], urban: OR = 1.12, [0.95, 1.33]). Both urban and rural VDC recipients were significantly less likely to be admitted to VA nursing homes, compared to those receiving other purchased care services (rural: OR = 0.42, [ 0.30, 0.58]; urban: OR = 0.58, [0.44, 0.78]). VDC receipt was not significantly related to changes in hospice admissions for either rural or urban Veterans. CONCLUSIONS: VDC recipients had fewer incidents of potentially avoidable health care use, compared to similar patients receiving other purchased care services. These benefits were more pronounced among rural VDC recipients than urban VDC recipients. IMPLICATIONS FOR POLICY OR PRACTICE: The VDC program is valuable for supporting individuals with multiple chronic conditions, particularly for rural residents. VDC provides flexibility and choice in care options for Veterans living in rural areas where access to agency care is limited. PRIMARY FUNDING SOURCE: Department of Veterans Affairs.